2006
DOI: 10.1016/j.jcrs.2006.01.106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic acrylic and plate-haptic silicone intraocular lens implantation in diabetic patients

Abstract: In diabetic patients, hydrophobic acrylic IOLs can lead to an increased flare in the early postoperative period but they seem to be more favorable than plate-haptic silicone IOLs because the latter lead to more PCO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Hydrophobic lens material has lower PCO and ND: YAG laser treatment rate than the hydrophilic lens. [20212223] Hydrophilic lens used in this study had 360° square edge, which has been reported to prevent PCO. [13] The only remaining factor of this study is the incidence of multiple striae, leading to the PCO development.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophobic lens material has lower PCO and ND: YAG laser treatment rate than the hydrophilic lens. [20212223] Hydrophilic lens used in this study had 360° square edge, which has been reported to prevent PCO. [13] The only remaining factor of this study is the incidence of multiple striae, leading to the PCO development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed to be the lowest with acrylic IOLs (10). The incidence of ACO and contraction is high in eyes with retinitis pigmentosa (11) and in diabetic patients (12). Werner et al have clinically graded ACO from 0 to IV (10).…”
Section: Anterior Capsule Opacification (Aco)mentioning
confidence: 99%